Parental knowledge and attitudes toward food allergies: a cross-sectional study on determinants and educational needs - Sari Taha; Raya Rabaiah; Alaa Dweikat; Lama Abu-Ali; Hala Yaeesh; Razan Jbour; Samah W. Al-Jabi; Sa'ed H. Zyoud (BMC, 2024)
Abstract Background Food allergy (FA) may often lead to fatal consequences if it is treated promptly. Parents of children with FA should have adequate knowledge to improve health outcomes and reduce the associated burden. This study aimed to examine the knowledge and attitudes regarding FA among parents of children with FA. Methods This was a cross-sectional study conducted among parents attending a primary healthcare center using convenience sampling. The minimum sample size of 280 was calculated using an equation based on the local prevalence of FA among children, and was increased to account for missing data. The data were collected using a four-section questionnaire that collected data about the parents and their children and included questions about knowledge and attitudes regarding FA. The knowledge score was calculated by summing the number of correct answers, with a maximum of 15 points. The Mann-Whitney and Kruskal-Wallis tests were used to examine the associations between the knowledge score and other variables. Spearman's correlation was employed to test the correlations between the knowledge score and other variables. Results A total of 381 parents completed the questionnaires, of whom 71.9% were mothers and 28.1% were fathers. The prevalence of food allergies was 14.22%. Almost one-third had children who had one or more types of FA (32.8%). Most of those patients had received a professional diagnosis of FA (75.3%). The median knowledge score was 7.0 (IQR = 6-8), with variable proportions of correct answers across and within topics. A higher knowledge score was significantly associated with parenting a child with FA (p = 0.006), comorbid asthma or eczema (p = 0.012), the preference to acquire information from professional health agencies (p < 0.001), and higher educational (p = 0.002) and income (p = 0.001) levels. Moreover, the number of discussions held with a healthcare professional regarding FA was significantly correlated with the knowledge score (r = 0.210, p = 0.019). Online resources were the most commonly reported source of information (65.4%). Parents believed that having a child with FA can cause stress in the family (76.1%) and impact siblings' daily lives (66.7%), while only a minority viewed FA as stigmatizing. Additionally, the majority encouraged governmental spending on FA research (92.9%). Conclusions Parenting a child with FA, comorbid asthma or eczema, number of discussions held with healthcare professionals, and education and income levels were significantly associated with a higher knowledge score. Educational interventions targeting parents should blend emotional regulation, medical information, and management skills to increase knowledge about FA and alleviate associated stress.